Significance in an idea industrial product (Journal of the College of Basic Education, 2022)
This study seeks to investigate the significance of the concept that is the design system represented by industrial products. And that this significance will reveal to us an aesthetic dialogue with the provisions of its functional and expressive language, and the research contributes to shedding light on the functional performance in industrial products. The first chapter included the research problem represented in what is the role of significance in building the idea of ​​​​designing industrial products? Hence its importance in dealing with significance And highlighting it in the designs of industrial products, down to the goal of revealing the role of significance and its role in highlighting the idea of ​​the industrial product. The limits of the study included industrial products from “Samsung Company” that are available on the international network (Internet). During the period from (2013 AD) to the year ( 2014 AD)